(untitled) (KIUT Publication, 2025)
This article explores the essence of PTC (Photovoltaics for Utility-Scale Applications) test conditions and highlights their advantages compared to the STC standard. The authors analyze the closeness of PTC parameters to real operating conditions, the efficiency of photovoltaic modules, temperature coefficients, and the procedures for independent laboratory evaluation of test results. The article also discusses methods for determining module quality and efficiency using the PTC/STC ratio, as well as the differences between branded and low-cost modules. This approach helps make more accurate decisions when selecting solar panels.